2015
DOI: 10.1080/00330124.2015.1054020
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in the Association between Common Mental Disorders and Regional Deprivation in Ireland

Abstract: This paper aims to add a gender and place perspective to our understanding of depression and anxiety (common mental disorders, CMD) through the use of multilevel models. To date, regional variations in the prevalence of CMD in Ireland have not been explained adequately.Using data from the 2007 Quarterly National Household Survey special module on health and health service utilization, this paper examines whether regional differences in CMD persist after accounting for both individual and regional characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Although other studies have shown that the places where people live have a substantial impact on health, 15 16 studies on the links between area deprivation and mental disorders among men and women, separately are limited. A recent, large, population-based study 18 of over 21 000 people living in Ireland showed that area deprivation was associated with a significantly increased risk for common mental disorders in women, but not in men, after controlling for demographic and socioeconomic factors. In line with this, a study 21 of over 2700 adults living in Canada showed that greater neighbourhood disadvantage also was associated with increased risk of depressive symptoms in women, but not in men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although other studies have shown that the places where people live have a substantial impact on health, 15 16 studies on the links between area deprivation and mental disorders among men and women, separately are limited. A recent, large, population-based study 18 of over 21 000 people living in Ireland showed that area deprivation was associated with a significantly increased risk for common mental disorders in women, but not in men, after controlling for demographic and socioeconomic factors. In line with this, a study 21 of over 2700 adults living in Canada showed that greater neighbourhood disadvantage also was associated with increased risk of depressive symptoms in women, but not in men.…”
Section: Discussionmentioning
confidence: 99%
“… 17 Population-based studies further showed that living in disadvantaged neighbourhoods or places where there is high chronic stress can increase the risk for mental disorders, such as depression. 18–20 Whether area deprivation can be used to predict GAD is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to the absence of clinical measures of depression in the Airwave dataset, self-reported depression was used. Regarding the validity of self-reported measures, research has found that self-reported data is a valid method to capture the health outcomes in epidemiology (Morrissey, 2016). As such, self-reported doctor-diagnosed depression is a widely used measure of depression (Bishwajit et al, 2017;Morrissey, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the validity of self-reported measures, research has found that self-reported data is a valid method to capture the health outcomes in epidemiology (Morrissey, 2016). As such, self-reported doctor-diagnosed depression is a widely used measure of depression (Bishwajit et al, 2017;Morrissey, 2016). A police study has also used a self-reported measure of depression to study depression in police officers (Wang et al, 2010).…”
Section: Methodsmentioning
confidence: 99%